The theological significance of an analysis of the meaning of love from the perspective of the philosophy of theology - Strauss, DFM (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
The aim of this article is to explore the structural features of love as succinctly captured in the sketch below. In order to achieve this goal attention will be given to a number of distinct but related issues. It will be argued that the core meaning of love primarily refers to a distinct aspect, mode or function or reality, namely the moral aspect (§3 and §4). Although it is unique and indefinable (§4 and §5), it intrinsically also coheres with all the other aspects of reality (such as the numerical, the biotical, the logical-analytical and the sign-mode) (§6). In order to account for this inter-modal coherence the nature of analogies and metaphors are elucidated (§7). Owing to its uniqueness the core meaning of the moral aspect (like all the other aspects) is irreducible (§5). The argument is extended by taking into account that every concrete (natural and social) entity and process has a typical function within the moral aspect of reality (partially §9 and §10). Moral subject-subject relations form the basis of the way in which Buber over-emphasized such relations (§3) and discussing his view will provide the possibility to show that moral subject-subject relations are indeed differentiated by multiple contexts (§3). Buber's influence on Aalders, Stoker and Heyns is seen in the restriction of the meaning of the ethical to subject-subject relations (§ 9). Only against this background it is possible to account for the richly nuanced meaning of love (§10). Finally an important epistemological distinction is related to the moral aspect, explaining the difference between conceptual knowledge and concept-transcending knowledge (§11). The overall picture that emerges from this analysis relates to all the academic disciplines, including theology. In the course of the argument the theological significance of some of the distinctions is highlighted.